KepuasanÂ PernikahanÂ Â DitinjauÂ dariÂ BerpacaranÂ dan TidakÂ Berpacaran - Ardhianita, Iis; Andayani, Budi (Faculty of Psychology, Universitas Gadjah Mada, 2005)
GettingÂ marriedÂ isÂ perceivedÂ asÂ anÂ important phaseÂ inÂ humanÂ lifeâ€cycle.Â JustÂ likeÂ fashion, marriageÂ hasÂ alsoÂ itsÂ ownÂ trendÂ orÂ mode.Â In IndonesiaÂ theÂ legendÂ of Â Siti Â Nurbaya illustratingÂ aÂ kindÂ ofÂ maritalÂ arrangementÂ in,Â at least,Â theÂ firstÂ halfÂ ofÂ theÂ pastÂ century.Â SuchÂ a trendÂ inÂ marriageÂ isÂ anyÂ moreÂ popularÂ theseÂ days. YoungÂ peopleÂ todayÂ mostlyÂ preferÂ toÂ marryÂ their ownÂ choices,Â thoseÂ alreadyÂ bondÂ inÂ engagement orÂ girlÂ orÂ boyÂ friendsÂ theyÂ alreadyÂ mate.Â Another kindÂ ofÂ trendÂ hasÂ appearedÂ recently.Â Some moslemsÂ preferÂ toÂ marryÂ withoutÂ theÂ phaseÂ of datingÂ orÂ engagement.Â SomeÂ evenÂ marryÂ ones chose,Â orÂ arrangedÂ byÂ theirÂ ustadzÂ (spiritual leader). TheÂ purposeÂ ofÂ thisÂ studyÂ isÂ toÂ findÂ out whetherÂ aÂ differenceÂ inÂ theÂ premarital relationship(withÂ versusÂ withoutÂ engagement orÂ dating)Â affectÂ couplesâ€™Â maritalÂ satisfaction. TheÂ resultÂ showsÂ thatÂ thereÂ isÂ aÂ very significantÂ differenceÂ inÂ maritalÂ satisfaction betweenÂ datingÂ andÂ nonâ€datingÂ couples. ExplanationÂ uponÂ theÂ phenomenonÂ discussed. Keywords:Â maritalÂ satisfaction,Â datingÂ and non datingÂ couples